Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.arr.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on cellular mechanotransduction

Abstract: Aging is becoming a critical heath care issue and a burgeoning economic burden on society. Mechanotransduction is the ability of the cell to sense, process, and respond to mechanical stimuli and is an important regulator of physiologic function that has been found to play a role in regulating gene expression, protein synthesis, cell differentiation, tissue growth, and most recently, the pathophysiology of disease. Here we will review some of the recent findings of this field and attempt, where possible, to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
60
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 229 publications
(310 reference statements)
0
60
0
2
Order By: Relevance
“…This outcome suggests that the overload due to the body weight, associated with the load to perform resistive exercise, should have induced sarcomerogenesis. According to Wu et al 25 mechanical loading and contractile activity play critical roles in the regulation of muscle mass and altered loading can lead to the structural remodeling of skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome suggests that the overload due to the body weight, associated with the load to perform resistive exercise, should have induced sarcomerogenesis. According to Wu et al 25 mechanical loading and contractile activity play critical roles in the regulation of muscle mass and altered loading can lead to the structural remodeling of skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies conducted to measure the motility as a function of age of fibroblast cells plated on flat substrates have indicated that there is a decrease in overall single-cell translocation with age (31). Wound healing in elderly individuals is hampered (32) by a cohort of factors including a decreased capacity to produce ECM components, such as collagens and elastins; increased collagen fragmentation; increased MMPs; reduced collagen solubility and increased fibrosis; a reduced rate of HIF-1α (hypoxia-inducible factor-1α) mRNA and HIF-1α production (33), which influence ECM production (2, 34); a decreased sensitivity to chemotactic and mechanical stimulation (35); reduced motility and translocation by single cells and clusters of cells (31, 34); a reduced proliferation and number of fibroblasts in older tissue; an increased ratio of senescent to normal cells (20); enhanced ROS (1); depleted adenosine triphosphate (ATP) generation (11); and reduced epithelialization (29). …”
Section: Mechanics and The Ecmmentioning
confidence: 99%
“…shear stress; endothelium; G protein-␣; inositol 1,4,5-trisphosphate receptor DISTURBED LAMINAR shear stress patterns, including retrograde flow, are known promoters of atherogenic signaling. These variations of hemodynamic parameters may occur naturally as a result of an increased vascular tone in the downstream resistant vessel beds, the geometrical nature of the vessels (anatomical curvature), or by the increase in diastolic retrograde flow often exacerbated with aging, hypertension, or obesity (40). It was recently shown that even at rest, older subjects exhibit greater brachial retrograde flow compared with younger subjects (30).…”
mentioning
confidence: 98%